Fundamentals of Knowledge: a Philosophy of Science Perspective - Muhammad Aceng Tata; Rohanda Rohanda; Abdul Kodir (Gunung Djati Conference Series, 2026)
The objective of this research is to analyze the vital role of logic in philosophical studies, particularly in understanding the nature of knowledge, the structure of truth, and its function within the contexts of life and education. The method used is a qualitative method employing a library research approach and descriptive-philosophical analysis to examine literature related to epistemology and logic. The results indicate that knowledge is the product of rational human activity, categorized into empirical, rational, intuitive, and scientific types. Structurally, logic serves as a primary tool to maintain the consistency and validity of reasoning that connects the knowing subject with the known object. Furthermore, theories of truth such as correspondence, coherence, and pragmatic theories serve as essential foundations for rationally assessing truth. The implications of this study emphasize that knowledge possesses a strategic function in underpinning decision-making and shaping critical, logical, and systematic mindsets in education.